A randomised controlled trial of a duodenal-jejunal bypass sleeve device (EndoBarrier) compared with standard medical therapy for the management of obese subjects with type 2 diabetes mellitus - Glaysher,M; Mohanaruban,A; Prechtl,CG; Goldstone,AP; Miras,AD; Lord,J; Chhina,N; Falaschetti,E; Johnson,NA; Al-Najim,W; smith,C; Li,JV; et al. (BMJ Open, 2017)
Introduction The prevalence of obesity and obesity-related diseases, including type 2 diabetes mellitus (T2DM), is increasing. Exclusion of the foregut, as occurs in Roux-en-Y gastric bypass, has a key role in the metabolic improvements that occur following bariatric surgery, which are independent of weight loss. Endoscopically placed duodenal-jejunal bypass sleeve devices, such as the EndoBarrier (GI Dynamics, Lexington, Massachusetts, USA), have been designed to create an impermeable barrier between chyme exiting the stomach and the mucosa of the duodenum and proximal jejunum. The non-surgical and reversible nature of these devices represents an attractive therapeutic option for patients with obesity and T2DM by potentially improving glycaemic control and reducing their weight.Methods and analysis In this multicentre, randomised, controlled, non-blinded trial, male and female patients aged 18–65 years with a body mass index 30–50 kg/m2 and inadequately controlled T2DM on oral antihyperglycaemic medications (glycosylated haemoglobin (HbA1c) 58–97 mmol/mol) will be randomised in a 1:1 ratio to receive either the EndoBarrier device (n=80) for 12 months or conventional medical therapy, diet and exercise (n=80). The primary outcome measure will be a reduction in HbA1c by 20% at 12 months. Secondary outcome measures will include percentage weight loss, change in cardiovascular risk factors and medications, quality of life, cost, quality-adjusted life years accrued and adverse events. Three additional subgroups will investigate the mechanisms behind the effect of the EndoBarrier device, looking at changes in gut hormones, metabolites, bile acids, microbiome, food hedonics and preferences, taste, brain reward system responses to food, eating and addictive behaviours, body fat content, insulin sensitivity, and intestinal tissue gene expression.